The effects of functional knee bracing and taping of the tibio-femoral joint in athletes with an ACL-deficient knee - Rahimi, Abbas (2001)
Aims: The aims of this study were to determine the usefulness of a functional knee brace (FKB) or a spiral method of taping in modifying the impaired biomechanics of the ACL-deficient knees towards a safe and more normal pattern, and to assess any compensatory changes at the ankle and hip joints following knee bracing or taping. The study also aimed to compare the difference in gait patterns during simple· level walking and treadmill activities for ACL-deficient subjects.